Perbandingan Performa Database Apache HBase dan Apache Cassandra Sebagai Media Penyimpanan Data Sensor Internet of Things - Dimas Malik Ibrahim; Rakhmadhany Primananda; Mahendra Data (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Nowadays, internet has dominated the world, millions of data is exchanged daily either through web/mobile apps or internet use involving the objects around us to be able to communicate each another (currently known as Internet of Things/IoT). IoT requires a database with a good performance to be used as its storage media. Good performance it is like fast inserting data process and high level of availability. There are two types of databases at this time, Relational Database and Not Only SQL (NoSQL) Database. NoSQL Database is the proper type to be used as data storage media on IoT system because it has better scalability and availability level than Relational Databases. Of the many NoSQL Database, the author chooses HBase and Cassandra to compare their performance in this research, because both are the best in database Column-based storage model. The authors test the Throughput, Latency, Runtime CPU Usage, and Memory Usage using JMeter and YCSB to compare the performance of both these databases. The results suggest that Cassandra has Throughput, Latency and Runtime that is better than HBase. Meanwhile, HBase has CPU Usage and Memory Usage better than Cassandra.